(untitled) (Journal of the College of Basic Education, 2022)
The research aims to( build instructional design - learning according to the average model Kolb and see its impact on the effectiveness of mathematical self-efficacy science students at the fourth), and achieve the objectives of research researcher experimental method was adopted, and use the experimental design posttest design of two unequal. Consisted sample of 65 students from fourth grade science students have been selected purposely, the sample was divided into two groups based on the results list learning methods for Kolb modified was the style Convergent is the highest ratio became the owners of this style, representing the experimental group and number (32) student who has studied design Education - learning and the rest representing the control group and the number (33) students who studied in the usual way. . Was aparity between the two sets of search variables (chronological age, previous achievement in mathematics ,previous information ,intelligence ,mathematical self-efficacy). The researcher to build an educational design - learning, according to the results of the learning styles of Kolb rate as the ( style Convergent) was the highest 48% of the total sample, and those who prefer to learn exploration Since the entrance systemic models that help exploration therefore followed the steps in the design, construction, as well as the building search tool of building a mathematical self-efficacy scale which consisted of (23) items included positive vertebrae and other negative and verify the authenticity of the construction by submitting it to the group of arbitrators and specialists in educational and psychological science and mathematics teaching, then the stability of the scale calculation and testing using Cronbach-alpha equation applied experience in Chapters the first and second semesters of the academic year 2014-2015m , as the researcher taught the two sets of empirical research on instructional design - learning and studied the control group according to the usual way. The dish mathematical self- efficacy of the two sets of research scale, and to test hypotheses collected data were statistically analyzed using statistical methods: (samples t-test for two independent samples and non-independent, and the of Cronbach- alpha equation, Pearson correlation ,coefficient, Jtman). and the search results: - There are differences statistically significant at the level of significance (0.05) between the mean scores of the experimental group and the control group in the mathematical self-efficacy in favor of the experimental group students measure. In light of the search results researcher came out with a number of conclusions and recommendations and proposals.